(untitled) (Studia theodisca, 2017)
This essay juxtaposes practices of sound storage in a World War I context with the contemporaneous use of sound in Dadaist poems and the ways in which Dadaists reimagine ethnographic discourse from a visual construct into an aural one. By focusing on the change in discursive genre that emerges with war-era attempts at creating a museum of sound, this essay sheds light on the changing place of the Other between national imperatives and colonial possession, as mediated through Dadaist practice.